Association between latent toxoplasmosis and bipolar disorder: a case-control seroprevalence study - Abdol Sattar Pagheh; Adele Sadat Talebian; Tooran Nayeri; Ali Akbar Esmaeili; Fatemeh Rezaei; Eisa Nazar; Masood Ziaee (BMC Infectious Diseases)
Abstract Background Toxoplasma gondii (T. gondii) is the most successful obligate protozoan that can infect warm-blooded vertebrate hosts. Some researchers suggest that the presence of Toxoplasma cysts in the brain can lead to mental disorders. Bipolar disorder (BD) is one of the serious neuropsychiatric disorders. Several studies have shown a high seroprevalence of T. gondii in bipolar patients. Therefore, this study aims to determine the prevalence of this infection in patients with BD. Methods In this case-control study, anti-Toxoplasma immunoglobulin (Ig) G and IgM antibodies were measured in serum samples from 115 patients with BD and 115 subjects without this disorder from the general population using commercially available enzyme-linked immunosorbent assay. Demographic characteristics of the patient and control groups, information about T. gondii infection and BD, and their potential risk factors were analyzed. We utilized the Mann-Whitney U test for continuous variables, the chi-square test for categorical data, and multivariate logistic regression to assess T. gondii infection and BD, with significance set at P < 0.05. Results Twenty-eight (24.34%) of 115 patients with BD and 10 (8.7%) of 115 controls had anti-T. gondii IgG antibodies. IgM antibodies against T. gondii were not reported to be positive in any participants. Furthermore, there was a statistically significant difference in the results [odds ratio (OR) = 2.89: 95% confidence interval (CI) = 1.08–7.73. P = 0.03]. Within the study population, various factors were identified as significant risk factors for BD: sex (OR 8.10, 95% CI 3.16–20.75), age 20–50 (OR 5.11, 95% CI 1.81–14.45), age over 50 (OR 19.54, 95% CI 4.02–94.89), education level (OR 0.24, 95% CI 0.09–0.60), working status (non-employment, OR 4.12, 95% CI 1.65–10.30), and income (middle, OR 0.29, 95% CI 0.10–0.89; high, OR 0.12, 95% CI 0.01–0.77), all with P-values less than 0.05. In addition, in the group of patients, there was no statistically significant relationship between T. gondii infection with the type of bipolar disease (P = 0.93), the severity of the disease (P = 0.61), and the history of suicide attempts (P = 0.63). Conclusion This study showed that toxoplasmosis is a risk factor for BD and increases the chance of developing BD. However, more studies with a larger sample size are recommended to clarify the development pathways of this disorder and provide new strategies for the prevention and treatment of this disease. Clinical trial Not applicable.